1974
DOI: 10.1037/h0035744
|View full text |Cite
|
Sign up to set email alerts
|

Is it time to lay the sleeper effect to rest?

Abstract: The "sleeper effect" has been defined as a delayed increase in the persuasive impact of a communication from a source low in credibility. This effect failed to appear in the present series of seven replications (total N = 656) of a sleeper effect experiment. However, the effectiveness of communications attributed to a source high in credibility did significantly decrease with passage of time when subjects were unprepared to counterargue with the communication. On the basis of these results and a retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 9 publications
(15 reference statements)
1
55
1
1
Order By: Relevance
“…Although, the dissociation hypothesis could be modified to explain these factors, it nonetheless appears to have abdicated its sleeper effect claims, and the "old" sleeper effect-the one that has been sought in experiments that merely presented a discounting cue before an otherwise effective message-remains dormant and moribund (cf. Gillig & Greenwald, 1974). However, a new differential decay interpretation, one that serves as a more powerful summary of the empirical results, has appeared as heir to the sleeper effect throne.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, the dissociation hypothesis could be modified to explain these factors, it nonetheless appears to have abdicated its sleeper effect claims, and the "old" sleeper effect-the one that has been sought in experiments that merely presented a discounting cue before an otherwise effective message-remains dormant and moribund (cf. Gillig & Greenwald, 1974). However, a new differential decay interpretation, one that serves as a more powerful summary of the empirical results, has appeared as heir to the sleeper effect throne.…”
Section: Discussionmentioning
confidence: 99%
“…A series of experiments conducted by Gillig and Greenwald (1974) is representative of many past sleeper effect studies. In their seven separate tests of the sleeper effect, which involved 656 subjects, Gillig and Greenwald found evidence for the relative sleeper effect but not for the sleeper effect proper.…”
Section: Logical Requirements Of the Dissociation Hypothesismentioning
confidence: 99%
“…The effects of variations in hard news consumption are virtually unchanged from Model 2. Some research-the so-called "sleeper effect" literature (see Gillig and Greenwald 1974)-suggests that individuals forget their own assessments of source unreliability (i.e., discounting cues) more quickly than the actual content of media messages (or at least disassociate the former from the latter). If so, media effects would increase over time, net of the erosion of the discounting cue.…”
Section: Possible Selection Effectsmentioning
confidence: 99%
“…Such a presumption would be correct, at least in part. For instance, Capon and Hulbert (1973) qualitatively reviewed the literature on the sleeper effect available at the time and concluded that the effect was so unreliable that researchers would be better off accepting the null hypothesis than continuing to further examine the phenomenon (for similar conclusions, see Gillig & Greenwald, 1974). Other reviewers, however, have cautioned against accepting the null hypothesis and have suggested that a careful review of past data, as well as rigorous theorizing testing would resolve the controversy Eagly & Chaiken, 1993;Gruder et al, 1978).…”
mentioning
confidence: 99%